Expedient Synthesis and Antibacterial Activity of Tetrahydro-1′H-spiro[indoline-3,4′-quinoline]-3′-carbonitrile Derivatives Using Piperidine as Catalyst - Vinoth, Nangagoundan; Vadivel, Pullar; Lalitha, Appaswami (Synlett, 2021)
A convenient synthesis of 2′-amino-7′,7′-dimethyl-2,5′-dioxo-1′-(phenylamino)-5′,6′,7′,8′-tetrahydro-1′H-spiro[indoline-3,4′-quinoline]-3′-carbonitrile derivatives has been designed using different substituted isatins, various 5,5-dimethyl-3-(2-phenylhydrazinyl)cyclohex-2-enones (arylhydrazones of dimedone) and malononitrile in ethanol with piperidine as catalyst at room temperature. The structures of the synthesized compounds have been elucidated by various spectroscopic techniques. The selected compounds have also been evaluated for their antibacterial activities against human pathogenic bacteria.
Keywords: antibacterial activity; base catalysts; quinolines; indoline; multistep synthesis